Farmers' social media groups for better extension and advisory services - Nodir Djanibekov; Zafar Kurbanov; Abdusame Tadjiev; Ajit Govind; Akmal Akramkhanov (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2023)
The spread of information and communications technology (ICT) in Central Asia has reached a point where most farmers use smartphones with mobile internet access providing an opportunity for a low-cost and timely access to agricultural information and advisory services. When extension service is poor and does not cater to the farmers' needs, farmers seek other sources of information, such as exchanging knowledge with their peers and engaging in social media groups using instant messaging applications (apps) such as Telegram and WhatsApp. Analysis of a farm-level survey conducted in 2022 in Kazakhstan and Uzbekistan, suggests that farmers' participation in online groups for information exchange is influenced by the enabling environment rather than by the type of cultivated crops or farm size. The findings are relevant for developing private sector strategies and public policies to spread digital technologies among Central Asia's farmers with a holistic plan for a digital transformation. When introducing smartphone- or web-based digital technologies, policymakers are recommended to start scaling up with younger and more technologically-savvy farmers who on the one hand rely on their own knowledge but on the other hand are more open to embracing new ways of farming and interaction. Decision-making autonomy is an important factor to facilitate digital transformation in agriculture in the Central Asian context.
urn:nbn:de:gbv:3:2-970601
Keywords: 330